Joomla! programming - Dexter, Mark, 1954- (Addison-Wesley, 2012)
When you master Joomla! programming, you can customize websites in ways that simply aren't possible by tweaking parameters or installing someone else's extensions. Now, there's an authoritative, 'soup-to-nuts' programming guide for every Joomla! user: from beginners with no Joomla! development experience to long-time coders seeking a quick start with Joomla!'s powerful new versions, 1.6, 1.7, and 2.5. Joomla! Programming presents proven best practices for getting the job done right. Written by Mark Dexter and Joomla! design architect Louis Landry (who wrote much of the new Joomla! framework), the text is packed with detailed examples and sample code, in-depth reference-style explanations available nowhere else, and fascinating sidebars revealing why Joomla! works the way it does. Both a tutorial and reference, this title brings together step-by-step instructions for everything from simple tasks (such as template overrides) to cutting-edge techniques involving components, MVC, and the Joomla! framework. You'll learn how to View Joomla! from a programmer's perspective Extend Joomla! with layout overrides, plugins, and modules Take full advantage of Joomla!'s improved new MVC implementation Build front-end and back-end components, from start to finish Secure your websites with Joomla!'s powerful, flexible new Access Control Lists Work with databases and use the new JDatabaseQuery to write complex queries Program Joomla! with JavaScript via the lightweight MooTools framework Develop custom category structures for your own websites and extensions Enable one-click updates for your own custom extensions Use the Joomla! platform as an application framework All example code, updates, and more information on Joomla! programming are available at the companion website, joomlaprogrammingbook.com.